IMPLEMENTATION OF CROSS-DISCIPLINARY RELATIONS IN THE LEARNING PROCESS HIGHER MATHEMATICS USING MS EXCEL - Honhalo , Nataliia (Physical and Mathematical Education, 2022)
Formulation the problem. In today's world, math education is an important component of training future engineers. The study of mathematics plays a key role in the educational system of vocational education: on the one hand, it acts as a system-creating link, significantly affecting the intellectual ability of students to learn; on the other hand, ensures the readiness of future professionals to apply mathematics in professional activities and other fields. This duality affects the choice of teaching methods and the formation of a set of problems in the teaching of mathematical disciplines. The article considers the implementation of cross-disciplinary links as one of the possible methods in teaching higher mathematics, which allows for the resolution of the existing contradictions between the differences in the acquisition of knowledge and the need for their application.Materials and methods. As a result of the study, a systematic analysis of the scientific, educational and methodological literature of the existing educational experience of using cross-disciplinary links to mathematical training of future engineers, generalization of own pedagogical experience of teaching the discipline "Higher Mathematics" for engineering students.Results. The method of realization of cross-disciplinary connections of higher mathematics and physics with the use of MS Excel on the example of an integrated practical lesson on "Solving systems of linear algebraic equations by Cramer's formulas and matrix method" for students majoring in "Power Engineering, Electrical Engineering and Electromechanics". An example of the application of linear algebra to solve engineering problems in the field of electrical engineering is the example of calculating currents in branched linear electric circuits. The importance of fundamental training and professional orientation of future engineers in the study of mathematical, general, and professional disciplines is emphasized.Conclusions. An important factor in the quality teaching of higher mathematics to engineering students is the implementation of cross-disciplinary links with other disciplines. The proposed methodological approach in conducting the above-mentioned integrated lesson allows significantly increases the interest of students in studying mathematics and contributes to the process of formation of professional and general competencies.
Keywords: mathematical education; Cramer's formulas; matrix method; branched linear electric circuit; cross-disciplinary connections; engineering education; integrated lesson; MS Excel tools